Characteristics of extreme precipitation over eastern Asia and its possible connections with Asian summer monsoon activity. (6th September 2018) - Cui, Danyang; Wang, Chenghai; Santisirisomboon, Jerasorn
Abstract : Frequently occurring extreme precipitation events have caused severe disasters over the years, especially in monsoon regions such as Southeast Asia and East China (SAEC). Understanding the characteristics of extreme precipitation in SAEC on annual and monthly scales is essential for improving predictions extreme precipitation events. In this study, the temporal and spatial distribution characteristics of extreme precipitation events in the summer half‐year (May to September) are analysed from 1986 to 2015 over SAEC, based on the threshold of extreme precipitation defined with a percentile method and the daily precipitation data from 190 meteorological stations. The results indicate that the precipitation in annual and summer half‐year over the SAEC are mainly attributed to extreme precipitation events. The frequency and amount of extreme precipitation are significant in South China and Southeast Asia, the Yangtze River region, and North China; specifically, the duration of high extreme precipitation events are longer in South China and Southeast Asia compared to those in other areas. The frequency and amount of extreme precipitation increased in South China, Southeast Asia and North China while have a decreasing trend in Yangtze River basin. Further investigation of the possible relationship between summer extreme precipitation events and the activity of the Asian summer monsoon (ASM) indicate that, the movements of extreme precipitation are consistent with the northward advance and southward withdrawal of summer monsoon and are commonly located in the vicinity of the front of the ASM. This phenomenon suggests that summer extreme precipitation events over SAEC are closely connected with ASM activity and may be the products of ASM. Abstract : The spatial distribution of (a) mean annual extreme precipitation (R95P), (b) mean annual extreme precipitation frequency, (c) annual total precipitation (PRCPTOT) and (d) the proportion of annual extreme precipitation to annual precipitation (PPER) over Southeast Asia and East China during 1986–2015. The black dots denote geographic distribution of 190 stations in Southeast Asia and East China.